Hubungan Rasio Neutrofil Limfosit (RNL) Dengan Lama Rawat Inap Pada Pasien Pneumonia Di Rumah Sakit Umum Daerah Dr. H. Abdul Moeloek Provinsi Lampung - Julianti, Dinul Aliya; Sangging, Putu Ristyaning Ayu; Pardilawati, Citra Yuliyanda; Tjiptaningrum, Agustyas (CV. Jasa Sukses Abadi, 2024)
Pneumonia is an acute infection of the lung tissue due to bacteria, viruses, and fungi. Increased RNL values in pneumonia patients are biomarkers to systemic inflammatory responses that are easily quantified, inexpensive, and easily interpretable in the prognosis of pneumonia patients associated with length of stay. However, there is still not much relevant amount of research, and its application in daily practice is still minimal. This study aimed to identify the relationship of NLR with the length of hospitalization in pneumonia patients. This study used a cross sectional design. The data collection technique is a total sampling with a sample size of 39 patients. The research location is at Dr. H. Abdul Moeloek Regional General Hospital, Lampung Province and will take place in July-December 2022. The independent variable is RNL, while the dependent variable is the length of stay. Data obtained from the results of laboratory supporting examinations in the medical records of pneumonia patients. The collected data were then analyzed using the Chi-square test with a CI of 95%. The results showed that the majority of patients came from the age group of 51-60 years (51.3%) and were male (61%). The average pneumonia patient had a high ANC value (9,260) and a normal ALC (1,244) so that a high NLR average (10,067) was obtained with an average long stay (6 days). There is a relationship between NLR and length of stay in pneumonia patients at Dr. H. Abdul Moeloek Regional General Hospital, Lampung Province (p<0.05).